Pengaruh Prokrastinasi Akademik Terhadap Hasil Belajar Siswa Kelas VII di MTs Miftahul Amal Bekasi - Abdul Hakim; Chientya Annisa Rahma Putrie; Sri Winarsih (Indo Publishing, 2025)
The purpose of this study was to determine how academic procrastination affects the social studies learning outcomes of seventh-grade students at MTs Miftahul Amal Bekasi. The phenomenon that many students have a tendency to persevere in completing academic assignments, which can impact their learning outcomes, formed the basis of this study. The research methodology used was an associative quantitative approach with a survey technique. The study population was 90 seventh-grade students at MTs Miftahul Amal Bekasi from the 2024–2025 academic year. A saturated sampling technique was used to select a sample of 60 students. A Likert-type academic procrastination scale and daily social studies test results were used to collect data. Basic linear regression was used for data analysis using SPSS version 20. The findings indicated that despite poor social studies learning outcomes, their academic procrastination levels were high. Academic procrastination had a significant impact on social studies learning outcomes, based on a regression test significance value of 0.000 (<0.05). Academic procrastination accounted for 97% of the variation in social studies learning outcomes, while other factors influenced the remaining 3%, based on a coefficient of determination (R2) of 0.970. These two variables had a very good relationship (R = 0.985). However, because increases in procrastination were accompanied by increases in learning outcomes in this study, the direction of the identified influence did not align with general theory. Despite the direction of influence revealed by most hypotheses, this study concluded that academic procrastination had a significant impact on social studies learning outcomes in seventh-grade students at MTs Miftahul Amal Bekasi. This opens up opportunities for further research to examine mediating factors that may influence this relationship, such as learning motivation, learning tactics, and contextual support.